Analysis of 4G Wireless Technology: Worldwide Wireless Web (wwww) - Naganjaneyulu, Dr. K. V; Siddiqui, Mohammed Ahsan; E, Sai Alekhya; K, Akshara (IJRDO -Journal of Computer Science Engineering, 2015)
In today’s era wireless services are the most preferred and dominating means of services of the world. The rapid increase in the service is due to the advancement of technology, especially the wireless technology. The worldwide revolution in mobile and internet technology have changed our way of living life. 4G will be the fourth generation of wireless networks, which is expected to dominate the current generations in the coming decades. In today’s technology of mobile networks and wireless systems most users are using 3G, which is the 3rd generation of mobile networks and almost every single user is enjoying this wonderful wireless technology. But a true confess is that most users are already waiting for the next generation of mobile networks, which is called 4G. This paper gathers and reviews the emerging 4G wireless technology which is coined as Worldwide Wireless Web (wwww)